(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article explores the influence of grammatical gender on translation practices, with a focus on cross-linguistic discrepancies between gendered and non-gendered languages. The analysis considers the cognitive, semantic, and sociolinguistic effects of grammatical gender and how these affect both literal and interpretive translation strategies. Special emphasis is placed on languages with rich gender systems such as Russian, German, and Spanish, and their translation into English, which lacks grammatical gender. The article highlights challenges in gender agreement, cultural nuances, personification, and gender-neutral translation trends.